(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:H. influenzae bacteria classified as type-able and non-type-able according to the presence or absence of capsule which is correlated with site of isolation. Objectives:To isolate H. influenzae from different clinical samples and differentiate both capsulated (type-able) and non-capsulated (non-type-able) one by molecular detection method and to make a comparison between the two types by cultural, molecular, and clinical aspects. Methods: A total of 220 clinical samples were aseptically taken from throat, ear, eye, sputum and CSF of patients attended three main hospitals in Hilla city, Iraq during the period from Feb. 2012 to Jun. 2012. All samples were subjected to bacterial cultivation, standard bacteriological method and molecular detection method. Other primers were used to detect the presence or absence of capsule using Bex A, Bex B, while p2 primer was used to detect non-type-able. Among capsulated one a specific primers (Hib, bex) targeting H. influenzae type b were used. Results:29 (13.2%) out of 220 clinical samples give presumptive detection and isolation of H. influenzae, of these only 10 (34.5%) were positive using X (haemin) and V (Nad) tests. Using PCR, only 6 out of 10 (60%) were positive, out of 6 isolates only 2 (33.3%) were capsulated (type-able) and 4(66.6%) non-type-able, out of 2 capsulated 1 (50%) was type b H. influenzae. Conclusion:Specific genetic marker should be used to detect both types. Many non-type-able H. influenzae isolates are also important cause of upper respiratory tract diseases including pharangitis, otitis media, and conjunctivitis. Using serotype specific gene targeting type b (Hib) is important among patient with meningitis and lastly separation between type-able and non-type-able according to the site of isolation. Keyword: H. influenzae , genetic marker, serotype specific gene, Hib, Bex( A, B) P6, NTHI, X,V factors